PERANCANGAN E-LEARNING MENGGUNAKAN PHP MYSQL PADA SMP MUHAMMADIYAH CIMANGGU - Muniroh, Nur; Subekti, Krisna (STMIK Komputama Majenang, 2020)
We all realize and feel that today the world is moving fast towards the formation of a science-based society, science-based business activities and the realization of a new culture based on science and technology, especially information and communication technology or also known as information and communication technology whose main form is the internet. One form of using internet technology to support the learning process is E-Learning. With this E-Learning, educators or tutors can put learning materials, give assignments, collect assignments, and quizzes for evaluation. In the process of this research, the author uses a methodology that is commonly used by other research, the methodologies used include the method of literature study, observation, interviews with teachers, and literature studies. The purpose of this paper is to create a web-based learning media (e-Learning) that can be used by teachers as a learning tool with various sources for providing learning materials. The results achieved are the authors try to design a web-based learning media or better known as E-Learning. It is hoped that later the school can implement this E-Learning so that it can improve the performance of teachers as teachers and increase the absorption of students in mastering the material. The conclusion of this paper is that with E-Learning teachers and students are given convenience in the teaching and learning process and increase creativity for teachers and students.